The perceived impact of falling and the fear of falling on older adults living independently at a continuing care retirement community in eastern north carolina - Berry, Caroline R. (East Carolina University, 2010)
This study was completed using the phenomenological research strategy to understand the effect that falling and the fear of falling has on independently living residents at a continuing care retirement community in eastern North Carolina. To understand the residents' perspectives, interviews, the Mini Mental State Exam [MMSE], and a poetry exercise were employed. The residents completed one to two interviews, lasting approximately 45 minutes in length, took the MMSE, and wrote down key words and phrases regarding their singular perspectives on falling and the fear of falling. Fifteen men and women, aged 78-94, participated. The researcher used the interviews, the MMSE, the poetry activity, field notes, the researcher's journal, blueprints and other facility-related information, and observation to construct a particular description of falls, the language used regarding falls and the fear of falling, the relevance of the physical environment, and activities, roles, and routines each participant had related to falls and the fear of falling.
Keywords: Accidental Falls; Occupational Therapy; Geriatrics